Pediatricians, Well-Baby Visits, and Video Intervention Therapy: Feasibility of a Video-Feedback Infant Mental Health Support Intervention in a Pediatric Primary Health Care Setting - Facchini, Sergio; Martin, Valentina; Downing, George (Frontiers in Psychology, 2016)
This case series study evaluated the feasibility and acceptability of a behavioral/cognitive psychological intervention in a pediatric primary health care setting during standard well-baby visits. The aim of the intervention was to support caregivers’ sensitivity and mentalization in order to promote infant mental health. Four neonates from birth to eight months were consecutively enrolled to test a short video-feedback intervention (Primary Care - Video Intervention Therapy, an adaptation of George Downing's Video Intervention Therapy to primary care) conducted by a pediatrician. The five minute interaction recording and the video-feedback session were performed during the same well-baby visit and in the same pediatrician's office where the physical examination was conducted. During the study period, six video-feedback sessions were performed for each baby at different ages (1, 2, 3, 4, 6, 8 months). Filmed and discussed were a series of different interactional situations: touch, cry, affective matching, descriptive language, feeding, separation and autonomy. The intervention was easily accepted and much appreciated by all four families enrolled. This study aimed to answer a dilemma which pediatric providers generally face: if the provider wishes to respond to not only physical but also infant mental health issues, how on a practical level can this be done? This case series study indicates that Primary Care - Video Intervention Therapy deserves to be seen as a promising new tool for such a purpose.